Risk factors and outcomes for carbapenem-resistant Klebsiella pneumoniae bacteremia in onco-hematological patients - Liu, Jianling; Wang, Haichen; Huang, Ziyan; Tao, Xiaoyan; Li, Jun; Hu, Yongmei; Dou, Qingya; Zou, Mingxiang (The Journal of Infection in Developing Countries, 2019)
Introduction: Carbapenem-resistant Klebsiella pneumoniae (KP) serves as a major threat to onco-hematological patients, resulting in great morbidity and mortality. The purpose of our study was to identify the risk factors for KP bloodstream infections (BSIs) and mortality in onco-hematological patients. Methodology: A retrospective observation study was conducted on KP BSIs in the onco-hematology departments at Xiangya hospital from January 2014 to September 2018. Multivariate analysis was employed to identify the independent risk factors for carbapenem-resistant (CR) KP BSIs and related mortality. Results: A total of 89 strains of KP were analyzed in our study, in which 20 strains were CRKP. The only risk factor for CRKP BSI was carbapenem exposure within 30 days before the onset of BSIs (HR 25.122). The 30-day mortality was 24.7%. CRKP caused more mortality than carbapenem-susceptible KP (55.0% vs 15.9%, P = 0.001). In the multivariate analysis, unresolved neutropenia (HR 16.900), diarrhea (HR 3.647) and RDW > 14% (HR 6.292) were independent risk factors for mortality, and appropriate empirical therapy (HR 0.164) was protective against mortality. Conclusions: Our findings showed that carbapenem resistance was spreading in our setting, and a precise combination of antibiotics covering the common pathogen is crucial to improving patient survival.